2015
DOI: 10.1200/jco.2013.49.3213
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cell Sarcoma Presenting As a Thyroid Mass

Abstract: A 44-year-old white woman with a history of Hashimoto's thyroiditis presented to her primary care physician for routine evaluation. A palpable right-sided thyroid nodule was noted. Ultrasound demonstrated heterogeneous enlargement of the thyroid with two 1 cm thyroid nodules (one hypoechoic, one isoechoic) in the lower pole of the right thyroid lobe. A 6-month follow-up ultrasound revealed a hypoechoic nodule measuring 2.7 ϫ 1.7 ϫ 2.2 cm (Fig 1A, gold arrow) with peripheral nodularity (Fig 1A, white arrowheads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…The patient in the present study only presented with an abdominal mass and did not present with any other obvious symptoms. The manifestations of the patient are similar to the cases reported in the literature (9,10). Follicular dendritic cells are essential in the lymph nodes, where their primary role is directed towards antigen presentation and antigen-dependent B-cell maturation.…”
Section: Discussionsupporting
confidence: 82%
“…The patient in the present study only presented with an abdominal mass and did not present with any other obvious symptoms. The manifestations of the patient are similar to the cases reported in the literature (9,10). Follicular dendritic cells are essential in the lymph nodes, where their primary role is directed towards antigen presentation and antigen-dependent B-cell maturation.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, promising results with gemcitabine and docetaxel were published (Conry, ). Due to limited data on cytogenetic (Perry et al , ) and molecular characteristics (Starr et al , ), few reports have demonstrated efficacy of targeted agents (Azim et al , ). Potential targets have been proposed, such as epidermal growth factor receptor (EGFR) (Sun et al , ).…”
mentioning
confidence: 99%
“…On the molecular level, Go et al 10 identified the BRAF V600E mutation, a potentially drugtargetable gain-of-function mutation that is variably present in other histiocytic and dendritic cell tumors, in a subset of follicular dendritic cell sarcoma tumors (18.5%, n = 27). In a case report of a rare, high-grade follicular dendritic cell sarcoma tumor of the thyroid, Starr et al 11 identified pathogenic loss-of-function mutations in PTEN (biallelic, nonsense) and TP53 (missense), and a novel missense mutation in RET using next-generation sequencing for a panel of 236 cancer genes. Griffin et al 12 recently provided the most comprehensive genetic analysis of follicular dendritic cell sarcoma to date using a targeted next-generation sequencing assay to profile mutational and copy-number status across 309 cancer-related genes in 13 tumors.…”
mentioning
confidence: 99%